Elogio de la Incertidumbre. La construcción de la confianza: entre la previsión y el desamparo. (santa fe, gobernación del río de la plata, siglo XVIII) - Tarragó, Griselda (2003)
This work highlights the creation of a network of merchants whose relationship was brought about not only by their commercial interests, but by diverse codes of honor and trust as well, thus allowing them to live in community. This investigation departs from the hypothesis that this type of relationship has a strong incidence as a structuring factor, and constitutes the action networks whereby people may even mitigate the rigors imposed by a relationship model created by the social actors.